2018
DOI: 10.1016/j.celrep.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Phosphorylation of the C Terminus of Hsp70 Regulates the Mitochondrial Import of SOD2 and Redox Balance

Abstract: SUMMARY The import of superoxide dismutase-2 (SOD2) into mitochondria is vital for the survival of eukaryotic cells. SOD2 is encoded within the nuclear genome and translocated into mitochondria for activation after translation in the cytosol. The molecular chaperone Hsp70 modulates SOD2 activity by promoting import of SOD2 into mitochondria. In turn, the activity of Hsp70 is controlled by co-chaperones, particularly CHIP, which directs Hsp70-bound proteins for degradation in the proteasomes. We investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Loss of this phosphorylation has the converse effect, triggering enhanced client degradation resulting from Hsp70-CHIP interaction (58). Similarly, another study demonstrated that the SBD of Hsp70 is phosphorylated by Akt1 at Ser-631, which decreases Hsp70-CHIP interaction (78). In this report, the downstream effect observed was to prevent degradation of superoxide dismutase-2 (SOD2) and promote the import of SOD2 into the mitochondria.…”
Section: Hsp70 Phosphorylation As Regulator Of Hsp70 Client Triagingmentioning
confidence: 60%
“…Loss of this phosphorylation has the converse effect, triggering enhanced client degradation resulting from Hsp70-CHIP interaction (58). Similarly, another study demonstrated that the SBD of Hsp70 is phosphorylated by Akt1 at Ser-631, which decreases Hsp70-CHIP interaction (78). In this report, the downstream effect observed was to prevent degradation of superoxide dismutase-2 (SOD2) and promote the import of SOD2 into the mitochondria.…”
Section: Hsp70 Phosphorylation As Regulator Of Hsp70 Client Triagingmentioning
confidence: 60%
“…glutathione (GSH) [18][19][20][21]. Continuous low-dose oxidative stress during ageing results in adaptive responses based on the activation of NF-kB and subsequently superoxide dismutases (SODs) with a key role played by the mitochondrial manganese superoxide dismutase (SOD2) [22,23]. In this process also heat-shock proteins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…À also has high reactivity and it can convert to other reactive oxygen species via cytochrome c oxidase, SOD and so on. 30,31 We noticed that triflate can react with O 2 À selectively and it is inert towards abundant intracellular reactive nucleophiles, such as amino acids and proteins that include reactive sulfur atoms under physiological conditions. 22 Thus, we selected triflate as the response unit for O 2 À detection due to its good selectivity, high sensitivity and rapid response.…”
Section: Establishment Of the Ddp Chemotherapy Cell Model Using An Admentioning
confidence: 99%